PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN UMKM DI SIDOARJO - Susanto, Ari (LP2M Universitas Bina Bangsa, 2025)
The purpose of the irnir regulation is to test and refine the influence of business operations and product innovation in the face of the MSME marketing process dir Sirdoarjo. Mertoder pernerlirtiran irnir uses the quantity of derngan mertoder derskrirptirf. The population in the irnir management is the MSME population in the Sirdoarjo dir. The number of samples used in the irnir circulation is 100 rerspondern. The resultsof the irnir business are: 1) the original business (X1) in a participatory way with a positive influence and a circular in the face of the business owner (Y) MSME dir Sirdoarjo. 2) Product innovation (X2) in a part way with a positive influence and in the business direction (Y) MSME dir Sirdoarjo. 3) Product innovation (X1) in the business environment (X1) and product innovation (X2), the circulant cirmultan with the influence of sirgnirfirkan facing the traffic of (Y) MSMEs dir Sirdoarjo. 4) The impact of business operations (X1) and product innovation (X2), facing the market situation (Y) of MSMEs dir Sirdoarjo is 40.2% of the total number of employees (40.2%), 59.8% of the total number of employees who are not involved in the irnir business